Articular Eminence Inclination and Glenoid Fossa Measurements by CBCT in Patients with Temporomandibular Joint Disorders - Hayder Mahdi Idan; Fawaz D. Al-Aswad (Diyala Journal of Medicine)
Background: The increasing frequency of temporomandibular joint dysfunction requires the promotion of diagnostic and therapeutic approaches. The several etiologies of dysfunction are still poorly understood. Numerous studies have talked articular eminence shape as a probable causative factor for this dysfunction.